Autonomía negociada: agencia y control en el trabajo contemporáneo - Mora-Salas, Minor; Recinas-López, Saúl (El Colegio de México, 2025)
This article analyzes how autonomy is configured in two emerging occupations in Mexico City: tattoo artists and app-based delivery workers. Using a comparative approach based on qualitative interviews, it explores how workers negotiate decision-making margins in contexts marked by precarity, algorithmic control, and public reputation systems. Despite belonging to different sectors, both groups share self-management of time, lack of labor rights, and individualized risk. Drawing from their experiences, we propose the concept of negotiated autonomy to describe a process where agency and control coexist in tension, enabling workers to construct meaningful relationships to their labor beyond the dichotomy of total subordination and complete freedom.